2011
DOI: 10.1523/jneurosci.5814-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Specific Adaptation in the Gerbil Primary Auditory Thalamus Is the Result of a Fast Frequency-Specific Habituation and Is Regulated by the Corticofugal System

Abstract: The detection of novel and therefore potentially behavioral relevant stimuli is of fundamental importance for animals. In the auditory system, stimulus-specific adaptation (SSA) resulting in stronger responses to rare compared with frequent stimuli was proposed as such a novelty detection mechanism. SSA is a now well established phenomenon found at different levels along the mammalian auditory pathway. It depends on various stimulus features, such as deviant probability, and may be an essential mechanism under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 44 publications
9
73
0
Order By: Relevance
“…The present human scalp recordings are consistent with previous results of frequency-specific adaptation in animals (Ulanovsky et al, 2003;Bäuerle et al, 2011;Taaseh et al, 2011), as well as with animal studies reporting response adaptation to statistical properties in the stimulation (Kvale and Schreiner, 2004;Dean et al, 2005Wen et al, 2009;Dahmen et al, 2010;Rabinowitz et al, 2011). Neurons along the ascending auditory pathway adjust to statistical properties such as mean and variance and to more complex stimulus distributional properties.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present human scalp recordings are consistent with previous results of frequency-specific adaptation in animals (Ulanovsky et al, 2003;Bäuerle et al, 2011;Taaseh et al, 2011), as well as with animal studies reporting response adaptation to statistical properties in the stimulation (Kvale and Schreiner, 2004;Dean et al, 2005Wen et al, 2009;Dahmen et al, 2010;Rabinowitz et al, 2011). Neurons along the ascending auditory pathway adjust to statistical properties such as mean and variance and to more complex stimulus distributional properties.…”
Section: Discussionsupporting
confidence: 91%
“…However, adaptation of neural activity can be separated into two types: stimulus-specific adaptation and adaptation to stimulus statistics. Stimulusspecific adaptation relates to reduced neural responsiveness due to sustained stimulation (Ulanovsky et al, 2003(Ulanovsky et al, , 2004Bäuerle et al, 2011;Taaseh et al, 2011). In the context of auditory spectral stimulation, it is also referred to as frequency-specific adaptation (Herrmann et al, 2013a(Herrmann et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…While a previous study showed that SSA does not depend on NMDA receptors, whereas MMN does (Farley et al, 2010), Taaseh et al (2011) suggested that, at least in auditory cortex, SSA shows true deviance detection, as does MMN. It is likely that biasing SSA toward the low-intensity domain of the FRA, as well as to the highest spectral continuum, might help to sharpen sound discrimination (hyperacuity), as suggested by Bitterman et al (2008). Future studies should analyze whether IC neurons are also sensitive to the violation of the regularity of the tone sequence caused by the presentation of the deviant stimuli (Jacobsen andSchroger, 2001, 2003), because there is growing and convincing evidence that the human auditory brainstem is able to encode regularities in the auditory stimulation history that serve to detect novel events Slabu et al, 2010Slabu et al, , 2012.…”
Section: Ssa Mechanisms and Functional Significancementioning
confidence: 99%
“…Collectively, these descending pathways are believed to mediate a number of adaptive phenomena such as signal-innoise detection (de Boer and Thornton 2008), tuning specificity (Bauerle et al 2011;Yan et al 2005), experience-dependent perceptual reweighting (Bajo et al 2010), and protection of the inner ear from acoustic trauma (Lauer and May 2011;Maison and Liberman 2000). Of the three systems, the olivocochlear projections are the best understood, thanks in part to recent studies that have taken advantage of the genetic tools uniquely available in the mouse.…”
Section: Introductionmentioning
confidence: 99%